Spirit Islam Santri Dalam Fatwa Jihad Pada Pertempuran Surabaya 1945 - Sugiarti, Sugiarti -; Suniah, Suniah; Kunah, Kunah (Indonesia, 2024)
During the Battle of Surabaya in 1945, the Islamic spirit of the Santris and the fatwa for jihad played a crucial role. The fatwa for jihad, which was infused with Islamic values, ignited the nationalist spirit among the warriors and citizens of Surabaya to resist the invaders. This research aims to: (a) understand the Islamic spirit of the santri in the context of the fatwa for jihad, (b) identify the factors driving the religious spirit of the santri, and (c) analyze the impact of the Islamic enthusiasm of the santri in the jihad fatwa on the 1945 Battle of Surabaya. This study adopts Kevin W. Fogg's Islamic spirit approach and utilizes a historical method that includes heuristics, critiques, interpretations, and historiography. Primary sources such as archives, contemporary newspapers, and various studies are utilized to uncover historical facts about the spirit of the Nahdlatul Ulama (NU) santri in response to the call for jihad. The research findings highlight how the Islamic spirit of the santri, shaped by their understanding of jihad based on faith in Allah and obedience to the kiai, influenced the fighting spirit of the santri, national unity, and war strategy, and garnered support from various circles in the Surabaya community. Finding of this research is how the Islamic spirit of the santri that animates their understanding of jihad based on faith in Allah and obedience to the kiai influences the fighting spirit of the santri, national unity, war strategy, and the support of the Surabaya community from various circles.